GABA Transport Modulates the Ethanol Sensitivity of Tonic Inhibition in the Rat Dentate Gyrus - Fleming, Rebekah L. (2011)
In recent years, the effect of ethanol on tonic inhibition mediated by extrasynaptic GABA(A) receptors (GABA(A)Rs) has become a topic of intensive investigation and some controversy. The high ethanol sensitivity of extrasynaptic GABA(A) receptors containing the δ subunit combined with the role of tonic inhibition in maintaining the background inhibitory ‘tone’ in hippocampal circuits has suggested that they may play a key role mediating certain behavioral effects of ethanol, including those related to learning and memory. We have found that ethanol disrupts learning and learning-related hippocampal function more potently in adolescent animals than in adults and that ethanol promotes extrasynaptic receptor-mediated GABAergic tonic currents more potently in adolescents than in adults. However, there have been no studies of potential mechanisms that may underlie the enhanced ethanol sensitivity of the tonic current in adolescents. In this study, we recorded GABA(A) receptor-mediated tonic currents in dentate gyrus granule cells in hippocampal slices from adolescent and adult rats. As previously reported, we found that ethanol potentiated the currents more efficaciously in cells from adolescents than in those from adults. We also found that the GAT-1 blocker, NO-711, eliminated this developmental difference in ethanol sensitivity. These findings suggest that regulation of ambient GABA by GABA transporters may contribute to the difference in ethanol sensitivity between adolescents and adults.